Mapping Strategy and Strategy Initiation Using the Strategic Management System and Performance Execution Excellence (SPEX2) - Fitrio, Harsyatria (Implementasi Manajemen & Kewirausahaan, 2024)
As a strategic commodity, sugar is always monitored by the government to ensure its availability at affordable prices. Indonesia faces three main problems with its sugar agribusiness: decreasing sugar productivity, increasing sugar imports, and instability in sugar prices in the domestic market because of inefficient distribution. To overcome this problem, PTPN I carried out a mapping of the sugar business and set targets that agreed with the government’s aspirations. This research uses a qualitative descriptive method by collecting primary data through in-depth interviews and observations related to strategy and performance execution excellence management systems (SPEX2). The research results show that PTPN I’s development strategy includes increasing operational efficiency, developing employee skills, and modernizing technology to increase productivity and sugar quality. The external strategy responds to opportunities and threats through government policies that support the development of the sugar industry. In addition, PTPN I focuses on financial, customer, internal business process, and learning growth perspectives, with increasing revenue, business development, and HR competency as top priorities.